UMP and PERHEBAT to help empower former army personnel - Mohd Ferdaus, Musa (2019)
Universiti Malaysia Pahang (UMP) and the Armed Forces Ex-Servicemen Affairs Corporation (PERHEBAT) are working together to empower former army personnel by providing skills training that will help them to have better economic standing.